2022
DOI: 10.1002/cta.3306
|View full text |Cite
|
Sign up to set email alerts
|

Isolated seven‐level inverter for grid‐connected power systems with predictive control method

Abstract: A novel isolated 7‐level (7L) multi‐level inverter (MLI) topology for grid‐connected medium and high voltage power applications is presented in this paper. The topology consists of two isolated transformers with different winding ratio and four switches connected to a single‐phase grid. This topology provides a great advantage over conventional MLIs by reducing passive and active components to allowing a 7L output voltage. Moreover, model predictive control (MPC) method is implemented to 7L‐MLI to generate gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Generally, it is not possible to precisely control the IOC according to the operator's requirements using simply OLO‐based PWM approaches. To regulate the IOC, authors have described the FCS‐PCCAs 3,4 . In Liu et al, 5 a robust MPC architecture based on fuzzy approximation has been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, it is not possible to precisely control the IOC according to the operator's requirements using simply OLO‐based PWM approaches. To regulate the IOC, authors have described the FCS‐PCCAs 3,4 . In Liu et al, 5 a robust MPC architecture based on fuzzy approximation has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…To regulate the IOC, authors have described the FCS-PCCAs. 3,4 In Liu et al, 5 a robust MPC architecture based on fuzzy approximation has been reported. In Hosseinzadeh et al, 6 generalized recommendations for implementing the FCS-MPC approach to handle different single-phase SCI topologies have been reported.…”
mentioning
confidence: 99%
“…The power generation using Solar Photovoltaic approach has become very familiar for the grid-connected and off-grid implementations in the energy arcade. [1][2][3] On the other hand, the future transmission is also hopefully moving forward with electric vehicles transportation system. 4 The usage of fuel cells as a source for the electric transportation system becomes popular.…”
Section: Introductionmentioning
confidence: 99%
“…In the emerging world, the renewable energy is an important factor and it plays a vibrant measure in the generation of energy. The power generation using Solar Photovoltaic approach has become very familiar for the grid‐connected and off‐grid implementations in the energy arcade 1–3 . On the other hand, the future transmission is also hopefully moving forward with electric vehicles transportation system 4 .…”
Section: Introductionmentioning
confidence: 99%